2013
DOI: 10.1371/journal.pone.0071595
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Analysis of the Ferret Fecal Viral Flora

Abstract: Ferrets are widely used as a small animal model for a number of viral infections, including influenza A virus and SARS coronavirus. To further analyze the microbiological status of ferrets, their fecal viral flora was studied using a metagenomics approach. Novel viruses from the families Picorna-, Papilloma-, and Anelloviridae as well as known viruses from the families Astro-, Corona-, Parvo-, and Hepeviridae were identified in different ferret cohorts. Ferret kobu- and hepatitis E virus were mainly present in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 70 publications
6
61
1
Order By: Relevance
“…This suggestion is supported by Aichivirus A infection in humans and a growing number of mammal species (Phan et al, 2011) as well as a recently reported kobuvirus closely related to Aichivirus A in an avian species (Pankovics et al, in press): the European roller (Coracias garrulus). Also Aichivirus B infection has been reported in several members of the Bovidae, including cattle (Bos Taurus), sheep (Ovis aries) and black goats (Capra aegagrus hircus) (Lee et al, 2012;Reuter et al, 2010) and one domestic carnivore, the ferret (Smits et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggestion is supported by Aichivirus A infection in humans and a growing number of mammal species (Phan et al, 2011) as well as a recently reported kobuvirus closely related to Aichivirus A in an avian species (Pankovics et al, in press): the European roller (Coracias garrulus). Also Aichivirus B infection has been reported in several members of the Bovidae, including cattle (Bos Taurus), sheep (Ovis aries) and black goats (Capra aegagrus hircus) (Lee et al, 2012;Reuter et al, 2010) and one domestic carnivore, the ferret (Smits et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Kobuvirus infection has been reported in three domesticated carnivores (the ferret, Mustela putorius furo, the domestic cat, Felis catus and the domestic dog, Canis lupus familiaris). The novel Kobuvirus described from ferrets in Europe belongs to the Aichivirus B species (Smits et al, 2013). Feline kobuvirus (FeKV) and canine kobuvirus (CaKV) belong to the Aichivirus A species.…”
Section: Introductionmentioning
confidence: 99%
“…3c). CroV1 was also distinct from ferret parechovirus, a recently discovered picornavirus distantly related to parechoviruses (Smits et al, 2013a), and clustered with swine pasivirus 1 and PLV-CHN, which are novel picornaviruses identified in piglets (Sauvage et al, 2012;Yu et al, 2013).…”
Section: Identification Of a Novel Picornavirusmentioning
confidence: 95%
“…The advent of highthroughput sequencing technology has enabled comprehensive approaches for the simultaneous detection of many viral genomes and the identification of unknown viral genomes without viral isolation (Firth & Lipkin, 2013). Using high-throughput sequencing, viral metagenomics approaches have elucidated whole enteric viromes, resulting in the discovery of unknown viruses in a variety of mammals, including non-human primates, bats, pigs, rodents, cats, sea lions, martens, badgers, foxes, ferrets and pigeons (Baker et al, 2013;Bodewes et al, 2013;Dacheux et al, 2014;Donaldson et al, 2010;Ge et al, 2012;Handley et al, 2012;Li et al, 2010bLi et al, , 2011bNg et al, 2014;Phan et al, 2011Phan et al, , 2013aShan et al, 2011;Smits et al, 2013a;van den Brand et al, 2012;Wu et al, 2012). Further molecular characterization has revealed high nucleotide sequence diversity and unique genome organization of novel viruses (Boros et al, , 2013Li et al, 2010a;Phan et al, 2013b;Sauvage et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Several pieces of evidences indicate that genetically highly similar kobuviruses circulate in domestic and wild animals: i) infection of wild boars by porcine kobuviruses has been documented in Hungary [15]; ii) a kobuvirus closely related to bovine kobuviruses (BKVs) (80.8-89.5 % aa sequence identity) within the species Aichivirus B has been identified in the rectal swab of a ferret [16]; iii) viruses resembling canine kobuviruses have been recently detected in different wild carnivore species, including red fox (Vulpes vulpes) [4], golden jackal (Canis aureus), sidestriped jackal (Canis adustus) and spotted hyena (Crocuta crocuta) [10]. More recently, kobuviruses closely related to members of the species Aichivirus A have been detected in a bird faecal sample, suggesting possible circulation of these enteroviruses between mammalians and avians [11].…”
mentioning
confidence: 99%